The Normative Standard for Future Discounting. Issue 3 (3rd July 2021) - Callender, Craig
ABSTRACT: This paper challenges the conventional wisdom dominating the social sciences and philosophy regarding temporal discounting, the practice of discounting the value of future utility when making decisions. Although there are sharp disagreements about temporal discounting, a kind of standard model has arisen, one that begins with a normative standard about how we should make intertemporal comparisons of utility. This standard demands that in so far as one is rational one discounts utilities at future times with an exponential discount function. Tracing the justification for this standard through economics, philosophy and psychology, I'll make what I believe is the best case one can for it, showing how a non-arbitrariness assumption and a dominance argument together imply that discounting ought to be exponential. Ultimately, however, I don't find the case compelling. Non-exponential temporal discounting is often rational. If this is correct, Instead of trying to 'fix' non-exponential discounting because it is irrational and associated with negative life outcomes, we might instead focus attention on why the conditions obtain that make such discounting rational.